Substance-induced anxiety disorder after one dose of 3,4-methylenedioxymethamphetamine: a case report - Kaeley Kaplan; Fiona Kurtz; Kelly Serafini (Journal of Medical Case Reports, 2018)
Abstract Background In this report, we describe a case of a patient with substance-induced anxiety disorder occurring after a single dose of 3,4-methylenedioxymethamphetamine. Furthermore, we describe the use and efficacy of the Primary Care Behavioral Health model, a collaborative approach to integrative primary mental health care, in evaluating and treating this rare mental health disorder. Case presentation Three days following ingestion of one dose of 3,4-methylenedioxymethamphetamine, a 35-year-old Hispanic man with no significant prior mental health history and no history of prior 3,4-methylenedioxymethamphetamine use presented to our hospital with severe, acute anxiety and panic symptoms. He was initially treated with a combination of behavioral therapy and the serotonin agonist buspirone. Buspirone ultimately proved ineffective, so it was discontinued in favor of the selective serotonin reuptake inhibitor sertraline. While awaiting the pharmacological onset of sertraline, the patient worked with a behavioral health consultant, who provided psychoeducation on the experience of panic, building relaxation skills, and modifying maladaptive thought patterns. Enhanced communication between the primary care provider and behavioral health consultant facilitated the planning and enactment of the patient’s care plan. Approximately 2.5 months after his initial ingestion of 3,4-methylenedioxymethamphetamine, the patient’s symptoms subsided. This improvement was attributed to the combination of the behavioral health intervention and sertraline at a dose of 50 mg daily. Six months after 3,4-methylenedioxymethamphetamine ingestion, the patient began to gradually taper sertraline and has had no resurgence of anxiety symptoms to date. Conclusions Our patient’s case not only demonstrates a rare presentation of 3,4-methylenedioxymethamphetamine-induced anxiety disorder but also provides support for the use of the Primary Care Behavioral Health model to deliver individualized, timely mental health care in a primary care setting.